Weak comultiplication modules over a pullback of commutative local Dedekind domains - Reza Ebrahimi Atani; Shahabaddin Ebrahimi Atani (Algebra and Discrete Mathematics, 2009)
The goal point of recent attempts to classify indecomposable modules over non-artinian rings has been pullback rings. The purpose of this paper is to outline a new approach to the classification of indecomposable weak comultiplication modules with finite-dimensional top over certain kinds of pullback rings.